37.4k views
4 votes
10. -3.8x - 5.9x = 223.1

User Gcq
by
4.9k points

2 Answers

3 votes

Answer:

x=-23

Explanation:

-3.8x-5.9x=223.1

Collect like terms by calculating the sum or difference of their coefficients

(-3.8-5.9)x

calculate the difference

-9.7x=223.1

Divide both sides of the equation by -9.7

-9.7x÷(-9.7)=223.1÷(-9.7)

Any expression divided by itself equals 1

x=223.1÷(-9.7)

x=-23

3 votes

Answer:

-23

Step-by-step explanation: You have to combine like terms first:

-3.8x -5.9x =223.1

-9.7x = 223.1

Then divide om each side of the equation by -9.7.

-9.7x/-9.7 = 223.1/-9.7

x =- 23

User Dazedandconfused
by
5.1k points